Experimental Study on Scale Control in Surface Pipelines by Magnetic Descaler - Muhammad Thaqif Bin Roslim, Muhammad Thaqif (2008)
This experimental study is conducted to investigate the applications of magnetic decsaler (MD) in scale control, which in particular focuses on the removal of scale. The experiment studied the effect of different MD configurations on scale removal and the effect of different flow velocity on scale removal using water as the solution.